2002
DOI: 10.1165/ajrcmb.26.4.4517
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 Inhibits Spontaneous Apoptosis in Human Eosinophils via Autocrine Production of Granulocyte Macrophage–Colony Stimulating Factor and Nuclear Factor- κ B Activation

Abstract: Prolonged eosinophil survival, i.e., reduced apoptosis, is implicated in the pathogenesis of chronic allergic inflammation. Here we demonstrate that interleukin (IL)-15, in the presence or absence of tumor necrosis factor (TNF)-alpha, reduces spontaneous apoptosis in freshly isolated human eosinophils. The prosurvival effect of IL-15 was abrogated by neutralizing antibody to granulocyte macrophage-colony stimulating factor (GM-CSF), although GM-CSF was not detected in conditioned media by ELISA. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 53 publications
2
43
0
1
Order By: Relevance
“…The role of ␥c-dependent cytokines on eosinophil survival has been studied to some extent before. In particular, IL-9 and IL-15 (21) have been implicated in enhanced eosinophil survival, whereas IL-2 and IL-4 showed no effects and might increase apoptosis, respectively. Moreover, recently IL-7 has been proposed to contribute to increased eosinophil survival in the airways (22).…”
Section: Discussionmentioning
confidence: 97%
“…The role of ␥c-dependent cytokines on eosinophil survival has been studied to some extent before. In particular, IL-9 and IL-15 (21) have been implicated in enhanced eosinophil survival, whereas IL-2 and IL-4 showed no effects and might increase apoptosis, respectively. Moreover, recently IL-7 has been proposed to contribute to increased eosinophil survival in the airways (22).…”
Section: Discussionmentioning
confidence: 97%
“…Eosinophils were isolated from mildly allergic donors and cultured according to Hoontrakoon et al (2). To summarize, cells were isolated by a negative immunomagnetic procedure and transferred to 5-ml polypropylene tubes in 1-ml aliquots (0.5 million/ml), and cultured in Iscove's medium (Life Technologies, Grand Island, NY) with 20% FCS (HyClone Laboratories, Logan UT).…”
Section: Eosinophil Isolation and Culturementioning
confidence: 99%
“…Prosurvival HGSFs, and particularly GM-CSF, have been implicated in inhibiting eosinophil apoptosis in vitro and in vivo (2,4,5,12,44). It has been shown that IL-5 (in the absence of GC) inhibits Bax activation/translocation, mitochondrial damage, cytochrome c release, caspase activation, and subsequent apoptosis (10,12).…”
Section: Gm-csf Addition Inhibits Gc-induced Mitochondrial Damage Andmentioning
confidence: 99%
“…It has been appreciated for some time that IL-3, granulocytemacrophage colony-stimulating factor and IL-5 enhance eosinophil survival and therefore eosinophil persistence in the tissues may be prolonged in their presence. Additionally, IL-13 (Luttmann et al 1996, Horie et al 1997, IL-9 (Gounni et al 2000) and IL-15 (Hoontrakoon et al 2002) have all been shown to enhance eosinophil survival. The significance of these findings is emphasised by ample evidence that these cytokines are present in asthmatic airway tissue and that eosinophils isolated from patients with atopic dermatitis and, to a lesser extent inhalant allergy, displayed enhanced survival compared with normal controls (Wedi et al 1997).…”
Section: Eosinophil Apoptosismentioning
confidence: 99%